Impact of capped and uncapped abandoned leads on the heating of an MR‐conditional pacemaker implant. Issue 1 (16th January 2014) - Mattei, Eugenio; Gentili, Giulia; Censi, Federica; Triventi, Michele; Calcagnini, Giovanni
<x xml:space="preserve">Abstract</x> Purpose To assess the risk of radiofrequency (RF) ‐induced heating in patients with MR‐conditional pacemaker (PM) systems, in the presence of another lead abandoned from a previous implant. Methods Four commercial pacemaker leads were placed beside a MR‐conditional PM system, inside a human trunk simulator. The phantom has been exposed to the RF generated by a 64 MHz body bird‐cage coil (whole‐body specific absorption rate [SAR] = 1 W/kg) and the induced heating was measured at the tip of the abandoned lead and of the MR‐conditional implant. Configurations that maximize the coupling between the RF field and the leads have been tested, as well as realistic implant positions. Results Abandoned leads showed heating behaviors that strongly depend on the termination condition (abandoned‐capped or saline exposed) and on the lead path (left or right positioning). Given a whole‐body SAR = 1 W/kg, a maximum temperature rise of 17.6°C was observed. The presence of the abandoned lead modifies the RF‐heating profile of the MR‐conditional implant: either an increase or a decrease in the induced heating at its lead tip can occur, mainly depending on the relative position of the two leads. Variations ranging from −63% to +69% with respect to the MR‐conditional system alone were observed. Conclusion These findings provide experimental evidence that the presence of an abandoned lead poses an additional risk for the patient implanted with a MR‐conditional PM system. Our results support the current PM manufacturers' policy of conditioning the MR compatibility of their systems to the absence of abandoned leads (including leads from MR‐conditional implants). From a clinical point of view, in such cases, the decision whether to perform the exam shall be based upon a risk/benefit evaluation, as in the case of conventional PM systems. Magn Reson Med 73:390–400, 2015. © 2014 Wiley Periodicals, Inc.